Electrochemical behavior of different preparations of plasma-sprayed hydroxyapatite coatings on Ti6A14V substrate - Souto, R. M. (2004)
The corrosion behavior of four different preparations of plasma-sprayed hydroxyapatite (HA) coatings on Ti6Al4V substrates in static Hank's balanced salt solution was investigated using dc potentiodynamic and ac impedance techniques. Two different nominal thicknesses, 50 m and 200 m, and two different spraying conditions, were considered. The electrochemical impedance experiments proved this technique to be very suitable for the investigation of the electrochemical behavior of surgical implant alloys when they are coated with HA, which is characterized by the dissolution and passivation characteristics of the underlying metal substrate. Because the coatings are porous, ionic paths between the electrolytic medium and the base material can eventually be produced, resulting in the corrosion of the coated metal. Differences in the corrosion resistance of the coated materials were detected, and a relevant model for the description of the coating degradation in the biosimulating solution was proposed. The model consisted of the description of the coated system in terms of a two-layer model of the surface film. Significant differences in electrochemical behavior for similar nominal thicknesses of HA coatings obtained under different spraying conditions were found